Motives for Selling Human Organs by Children in Indonesia - Josua Dariusman Zendrato; Kartina Pakpahan; Yusriando (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
ABSTRACT Children as one of the human resources and the next generation of the nation, should receive attention in the context of developing children. In connection with child development, legal facilities and infrastructure are needed that anticipate all problems that arise. There are many legal reasons why children are involved in murder cases followed by acts of mutilation. The biggest possibility is that it is easy for irresponsible parties to influence children to commit the crime of assisting premeditated murder. The purpose of this research is to understand the concept of legal responsibility for children who commit criminal acts, to find out the legal protection for children as perpetrators of criminal acts from the perspective of child protection law and to find out the application of the law to accomplices in the criminal act of selling human organs. The research carried out is normative legal research with a normative juridical approach taken from secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research and discussion, it explains the concept of legal responsibility for children who commit criminal acts, namely that they can be subject to criminal sanctions. Legal protection for children as perpetrators of criminal acts from the perspective of child protection law is by imposing a penalty of ½ (one-half) of the maximum criminal threat carried out by an adult. Children who commit crimes who assist premeditated murder cannot be sentenced to death or life imprisonment.